2021
DOI: 10.48550/arxiv.2111.00136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Information Processing With Integrated Silicon Carbide Photonics

Abstract: Color centers in wide band gap semiconductors are prominent candidates for solid state quantum technologies due to their attractive properties -optical interfacing, long coherence, spin-photon and spin-spin entanglement, and scalability. Silicon carbide color centers integrated into photonic devices span a wide range of applications in quantum information processing in a material platform with advanced availability and processing capabilities.Recent progress in emitter generation and characterization, nanofabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…In recent years, silicon carbide has gained interest for quantum technology applications in fields like communication [1][2][3][4] and (bio)sensing. 5,6 It was found that color centers in SiC have favorable properties, such as long-lived spin states and possibilities for operation at telecom wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, silicon carbide has gained interest for quantum technology applications in fields like communication [1][2][3][4] and (bio)sensing. 5,6 It was found that color centers in SiC have favorable properties, such as long-lived spin states and possibilities for operation at telecom wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years silicon carbide has gained interest for quantum technology applications in fields like communication [1][2][3][4] and (bio)sensing 5,6 . It was found that color centers in SiC have favorable properties, such as long-lived spin states and possibilities for operation at telecom wavelengths [7][8][9] .…”
mentioning
confidence: 99%